2014
DOI: 10.11648/j.ijsts.20140206.18
|View full text |Cite
|
Sign up to set email alerts
|

Peat Resources, Condition of Deposition as Well as their Utilization, Hakaluki Haor, Moulvibazar and Sylhet District, Bangladesh

Abstract: Abstract:The study area is the Hakaluki Haor which is the second largest wet land of Bangladesh. It spans over the districts of Moulvibazar and Sylhet in southeast Bangladesh. The study was focused in the exploration of peat reserve, reconstruction of the paleo-environment as well as the utilization of the peat resources. Peat is found randomly from 0.5 m to 7 m below the surface and 1 m to 11 m thickness at over 40 beels as well as small plain lands of 90 km2 area of Hakaluki Haor. The total reserve of peat i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, the volume of peat is very big. Masum et al (2015) reported the volume of peat to be 282 million ton in wet condition and 112 million ton in dry condition. Although other fuels may have higher calori c values but it would not be possible to get them in that bit amount of the Hakaluki Haor.…”
Section: Resultsmentioning
confidence: 99%
“…However, the volume of peat is very big. Masum et al (2015) reported the volume of peat to be 282 million ton in wet condition and 112 million ton in dry condition. Although other fuels may have higher calori c values but it would not be possible to get them in that bit amount of the Hakaluki Haor.…”
Section: Resultsmentioning
confidence: 99%